Impact of multiple infections on risk of incident dementia according to subjective cognitive decline status: a nationwide population-based cohort study - Lee, Jung-Won; Kim, Mina; Kim, Hoseob; Kim, Sunghwan; Um, Yoo Hyun; Wang, Sheng-Min; Lim, Hyun Kook; Lee, Chang Uk; Kang, Dong Woo (Frontiers in Aging Neuroscience, 2024)
The interrelation between infections, Subjective Cognitive Decline (SCD), and dementia development is recognized, but not fully understood. This study explored the combined effect of specific infections and SCD on the risk of dementia.Objectives: To assess the influence of Helicobacter pylori, herpes simplex virus, varicellazoster virus, and human papillomavirus on dementia risk in individuals with varying cognitive statuses, especially focusing on those with and without SCD.Methods: A cohort of 1,100,540 participants aged 66 years from the Korean National Health Insurance Service was divided into cognitively preserved (CP, n=825,405) and SCD (n=275,135) groups. This study analyzed the effects of single, dual, and triple infections on the risk of overall dementia, Alzheimer's disease (AD), and Vascular Dementia (VaD) using incidence rates and hazard ratios.The SCD group consistently showed a doubled risk of dementia, particularly AD, regardless of the number of infections. In the initial data, both the presence and number of infections, especially in the CP group, were associated with an increased dementia incidence and risk; however, this correlation disappeared after adjusting for covariates, hinting at a possible protective effect.Our findings emphasize that, while SCD is a steadfast risk factor for dementia, the role of infections is layered, subject to various influences, and requires more comprehensive exploration to fully understand their impact on dementia development.